Pararhizobium sp. strains enhancing chilling stress tolerance and yield in tomato plants - Lucía Díaz-Narváez; Kostadin E. Atanasov; Ester Murillo; Rubén Alcázar (Plant Stress)
In temperate climates, low temperatures represent a significant stressor that adversely affects crop yield and production. Tomato (Solanum lycopersicum L.) is a subtropical crop cultivated in temperate regions. However, most tomato cultivars are sensitive to chilling temperatures, which limit their cultivation in colder regions. Some microorganism-based plant biostimulants have been reported to enhance abiotic stress tolerance in crops. In this study, we isolated two Pararhizobium sp. strains (44 and 128) and tested their potential to trigger chilling stress tolerance in tomato. Through transcriptional, metabolic and biochemical analyses we demonstrate that inoculation with strains 44 and 128 enhance chilling stress tolerance by stimulating the ICE1-CBF-COR cold stress signaling pathway at transcriptional level, improving reactive oxygen species (ROS) detoxifying capacity and boosting the biosynthesis of stress-protective metabolites, such as polyamines and reduced glutathione (GSH). Treatment of tomato plants with these strains under non-stress conditions also increased tomato fruit weight and quality attributes. These findings suggest that Pararhizobium strains 44 and 128 could be valuable biostimulants for improving chilling stress tolerance and crop yield.